Guidance, Training and Exercises for Responding to an Improvised Nuclear Device: First Receivers, Public Health. Issue 2 (February 2018) - Case, Cullen; Coleman, C. Norman; Bader, Judith L.; Hick, John; Hanfling, Dan
Abstract : Abstract: All large-scale emergencies and disaster incidents, including the detonation of an improvised nuclear device (IND), have life and death medical consequences. Responders must have realistic plans to save lives and reduce physical and psychological morbidity. Fifteen years after 9/11, considerable progress toward developing and implementing such plans has been made, but gaps in the management of response to an IND loom large. Another paper in this series reviewed gaps for first responders; this paper reviews gaps for first receivers and public health. Closing gaps requires the implementation of complex systems including: extensive medical planning concept of operations and agreement to cooperate at the federal, state, and local levels, including during exercises that produce iterative improvements of the plans; identification, training, and deployment of medical receivers with radiation medical expertise; capacity to acquire and manage medical information and disseminate it to where it needs to be; creation and deployment of sufficient diagnostic and therapeutic materiel, including a radiation laboratory network for hematology, chemistry, and radiation dosimetry; agreement on optimal medical algorithms and guidelines for using myeloid cytokines and other lifesaving materials; agreement to harmonize radiation terminology to minimize confusion; plans to disseminate appropriate and timely public messages from recognized experts to help the public understand the true risks of the incident as well as trust the effectiveness and fairness of the response; implementation of a major medical hospital surge capacity including screening and triage of survivors, transport of scarce resources to affected local areas, transport of patients and the general public away from highly affected areas; and commitment to engage, train, and prepare the national medical community so they feel safe and comfortable participating in a response to an IND, wherever and whenever it may occur.